Inverse Eigenvalue Problems for Singular Rank One Perturbations of a Sturm-Liouville Operator - Xuewen Wu (Advances in Mathematical Physics)
This paper is concerned with the inverse eigenvalue problem for singular rank one perturbations of a Sturm-Liouville operator. We determine uniquely the potential function from the spectra of the Sturm-Liouville operator and its rank one perturbations.